Pengaruh Penggunaan Media Macromedia Flash terhadap Kemampuan Bercerita Siswa - Arifin Tahir; Firman Hamzi; Nur Hafsah Yunus MS; Andriani . (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah IX Sulawesi, 2020)
Abstract. The research is threaded to know the effectiveness of Macromedia based Flash Learning in Bahasa Indonesia, so it can improve the retelling skills of students. Learning to use Macromedia Flash allows effective and innovative learning in schools, as students can play while learning. The research method used in this research is quasi experiment. The population in this study was the V-class student at SDN 007 Sidodadi, with the simple random sampling technique obtained by the VA class samples as experimental classes and the VC class as the control class. The instruments used in this study were the test of student learning results that were given before and after the study was conducted. The analysis of the data used in this research is the Independent sample T-Test. Based on the results of analysis and discussion, it can be concluded that there are significant differences in the learning of storytelling my experience sharing between students who use Macromedia Flash and without using Macromedia Flash on students Class V SDN 007 Sidodadi. It is shown the value of P value 0.001 < 0.05, then Ho is rejected.